Water affordability measures under multiple and non-exclusive sources in Latin America and the Caribbean - Roberto Martínez-Espi\~neira; María Pérez-Urdiales (Inter-American Development Bank (IDB), 2024)
Standard water affordability measures that only account for expenditure on piped water are unlikely to adequately capture the situation of all consumers in developing countries, who often experience water service quality issues and must rely on coping strategies. We construct and compare a series of water affordability ratios including coping costs, and we also adjust these ratios by normative judgements about the need for coping strategies. We use nationally representative household-level data from 18 countries in Latin America and the Caribbean, providing, for the first time, a regional perspective on water affordability. We show that the share of income devoted to water expenses substantially increases when we consider coping costs, particularly affecting the bottom 20% of the income distribution. These findings should be of interest to policymakers aiming at promoting access to safe and affordable water as we also identify the characteristics associated with water affordability issues.
Keywords: Q21; Q23; Q25; 330; water affordability; water quality issues; regulation; Latin America and the Caribbean